MicroRNA-150 inhibitors enhance cell apoptosis of melanoma by targeting PDCD4 - Wan, Jianji (Oncol Lett, 2018)
Malignant melanoma is a tumor with a high mortality rate. Previous studies have demonstrated that the oncogenesis of melanoma is associated with microRNA (miR)-150. However, the role of miR-150 in melanoma and its regulatory mechanisms are still unclear. In the present study, melanoma cancer tissues and adjacent normal tissues were obtained from 20 melanoma patients. The expression level of miR-150 in melanoma tissue and cell lines was detected by reverse transcription-quantitative polymerase chain reaction. miR-150 inhibitors/negative control were transfected into melanoma A375 cells in order to investigate the effects of miR-150 on cell proliferation, apoptosis, cell cycle migration and invasion using a Cell Counting Kit-8, colony formation, Hoechst 33528, flow cytometry, and Transwell assays. The association between miR-150 and programmed cell death protein-4 (PDCD4) was detected by a dual luciferase reporter assay. The functional role of PDCD4 in miR-150-affected melanoma cells was confirmed by small interfering (si)RNA knockdown. Results demonstrated that miR-150 was significantly upregulated and mRNA and protein expressions of PDCD4 were decreased in melanoma cancer tissues as compared with adjacent normal tissues. The level of PDCD4 was inversely associated with the level of miR-150. Transfection of miR-150 inhibitors suppressed cell proliferation, migration, and invasion, while the apoptosis of cells was promoted and G2/M cell arrest was induced. MiR-150 inhibitors enhanced the expression of caspase-8 and p21. The PDCD4 was identified as a direct target gene of miR-150. The effects of miR-150 inhibitors on apoptosis and apoptosis-associated proteins, including caspase-8 and p21, of A375 cells, were reversed following transfection of siRNA-PDCD4. Therefore, miR-150 inhibitors enhance cell apoptosis via upregulation of PDCD4-mediated activation of caspase-8 and p21. These findings demonstrate the potential for a promising therapeutic strategy in the management of melanoma.